PENGARUH VISKOSITAS TERHADAP DISTRIBUSI TEKANAN RADIAL PADA ALIRAN DI ANTARA DUA SILINDER KONSENTRIS VERTIKAL - -, Basyirun (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2007)
This research is conducted to know pressure distribution in the gap between the cylinder as function of R (flow radius) caused by velocity gradient on inside cylinder. Be-side, it is conducted to show the influence of viscosity pressure distribution in the gap cy-linders.This research is carried out in two concentric cylinders of 200 mm high. The in-side cylinder is rotated and the outer is fixed. The clearance of the cylinder is 10 mm. The fluid with varying viscosity (m1=9,86.10-5 kg/m.det.; m2=10,036.10-5 kg/m.det; m3=15,283.10-5 kg/m.det; m4=27.40.10-5 kg/m.det.) is filled into the gap. The inside cylinder is driven by a DC motor connected to a motor speed controller. The pressure is measured at the lower of the gap with three point in difference radius. The result show that the pressure in the gap of cylinder tends to decrease under atmospheric pressure. The highest decreasing tendency of pressure is near to the mea-surement point at inside cylinder. The result of the experiment shows that it has the sa-me phenomenon with theory, although there is a difference quantitatively.